Pemantauan Limbah Amonia Menggunakan Sistem IoT Berbasis Android - Indriaswari, Raden Ayu Janica Rahmaditha; Mardhiyyah, Rodhiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The development of the urea fertilizer industry in increasing fertilizer production has had negative impacts, especially related to the increase in ammonia waste which can endanger the health of local communities. To overcome this, a warning system was developed that can monitor and manage the spread of ammonia in the environment. This system uses data analysis methods and sensor technology to detect dangerous ammonia levels and provide real-time information to the public. With a warning system in place, companies can take immediate action to control waste, prevent further negative impacts, and support sustainability efforts. Apart from that, this system also increases public awareness of the importance of maintaining air quality and health, as well as encouraging company transparency regarding the resulting environmental impacts. It is also hoped that the community's active role in monitoring can strengthen relations between the company and local residents.